Design and Implementation of Thermostat (Digital and Mercury) - muhsen, Mohammed ali; Hasan Alwan, Ahmed Thamer; Fadhil, Ali mahdi; ali, Saja tareq; Mustafa, Youssef Khader Hussein (American Journal of Biodiversity, 2025)
Digital thermometers :- Digital thermometers work by using heat sensors that determine body temperature and display reading numerically on the digital screen.Digital thermometers can be used to take temperature readings in the mouth, rectum, or armpit.Oral temperature can be measured by either a digital or mercury thermometer Mercury thermometers: - Mercury thermometers are mercury-in-glass thermometers. Do not use mercury thermometers; they can break, releasing small fragments of glass and highly poisonous mercury. Working Principle of the Device: - Digital thermometer is a less hazardous instrument use for taking/recording temperature from a specific body. It works just like a liquid in glass thermometer but in a different way because of its accuracy in reading, the temperature of the given body is taken by the temperature sensor (LM35) and feed into the microcontroller (PIC16F877A) where the conversion takes place. The ADC port of the microcontroller(PIC16F877A) is interfaced with the temperature sensor which allows it to have direct access to the temperature reading from the sensor, the reading taken from the temperature sensor is been processed by the microcontroller to be given as an output on the LCD display screen. The LCD displays the processed data given to it by the microcontroller while the potentiometer is used as contrast level changer for the LCD (increase and decrease level of brightness for the LCD screen). The oscillatory circuit works at 8 MHz rate and it serves as clock counter for the microcontroller allowing the microcontroller to mead between logic 1 and 0 synchronously. Mercury thermometer work on the principle :- of thermal expansion of liquids. In case of mercury thermometer, mercury (liquid) expands when the temperature increases. This rise in the level of mercury gives the temperature readings. Children’s decisions concerning investigation and treatment may be based on the results of temperature alone. Although the accuracy of axillary temperature measurement is affected by a number of factors, device dwell time and device type are common. Objective. Compare body temperature between glass mercury thermometer (GMT) and digital thermometer (DT). Method. Comparative descriptive study was used. A total of 101 samples were taken with convenient sampling technique, but 98 were analyzed. Statistical significance (???? < 0.01) and clinical significance (MD ≥ 0.2∘C) were used in the analyses. Correlations and Bland-Altman plots were used to observe agreements of the recording. Results. Mean difference (MD) of 10 min GMT and DT was 0.13 ± 0.11. Statistically significant differences were noted in 10 min GMT and DT (???? < 0.00). But the correlations were strong positive (???? > 0.75) and all MD were at the limit of agreement in Bland-Altman plot. Clinically, it is not significant (MD < 0.2∘C). Conclusion and Recommendations. Even though statistical significant differences (???? < 0.001) were noted between 10 min GMT and DT, the strong correlation, good agreements, and clinical insignificances make DT good alternative to the traditional GMT. Their variation in temperature is not likely to change any clinical decision. So, health professionals should use DT for measuring body temperature in under-5 febrile illnesses